2019
DOI: 10.1038/s41598-019-43884-2
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 4 inhibition alters chemokine receptor expression and T cell trafficking

Abstract: Aquaporins (AQPs) are water channels that mediate a variety of biological processes. However, their role in the immune system is poorly understood. We recently reported that AQP4 is expressed by naïve and memory T cells and that AQP4 blockade with a small molecule inhibitor prolongs murine heart allograft survival at least partially through diminishing T cell activation, proliferation and trafficking. The goal of this study was to determine how AQP4 function impacts T cells in the absence of antigen stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Aquaporins can coordinate migration in some settings by harnessing osmotic pressure ( Stroka et al, 2014 ), and treating mice with a putative inhibitor of aquaporin 4 results in potent lymphopenia without changes in splenic T cell numbers, consistent with an egress block. These alterations were attributed to changes in gene expression, but a direct role for aquaporins in egress was not ruled out ( Nicosia et al, 2019 ). In our hands, T cells poorly tolerated inhibitors of aquaporins and solute transporters, precluding studies aimed at determining a role for osmolarity in S1P-induced pressurization or blebbing.…”
Section: Discussionmentioning
confidence: 99%
“…Aquaporins can coordinate migration in some settings by harnessing osmotic pressure ( Stroka et al, 2014 ), and treating mice with a putative inhibitor of aquaporin 4 results in potent lymphopenia without changes in splenic T cell numbers, consistent with an egress block. These alterations were attributed to changes in gene expression, but a direct role for aquaporins in egress was not ruled out ( Nicosia et al, 2019 ). In our hands, T cells poorly tolerated inhibitors of aquaporins and solute transporters, precluding studies aimed at determining a role for osmolarity in S1P-induced pressurization or blebbing.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that inhibition of AQP4 expression resulted in slowed tumor growth ( Ding et al, 2011 ; Ding et al, 2013 ). Nicosia et al ( Nicosia et al, 2019 ) found that both CD4 + and CD8 + T cells expression AQP4. T cell proliferation, trafficking and activation were stunted as a result of AQP4 blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine-dependent T-cell migration seems to require AQP3-mediated H 2 O 2 uptake [338]. The inhibition of AQP4 with AER-271 in mice T-cells reduced the expression of key chemokine receptors (S1PR1, CCR7) and impaired chemotactic activation [339]; however, evidence for this agent as a selective AQP4 inhibitor is equivocal, and the effects could reflect the inhibition of IKKβ and NF-κB signaling [340]. Phagocytosis, an ultimate defense mechanism, is supported by AQP3-mediated glycerol flux in macrophages during phagosome formation [341].…”
Section: Inflammatory and Immune Responsesmentioning
confidence: 99%